Structural and electrochemical properties of nickel-cobalt oxide/activated carbon for supercapacitor application - Chang, Sook Keng (2012)
Co-precipitation method was adopted in the preparation of nickel-cobalt oxides for potential application in supercapacitors. The formation of spinel nickel-cobalt oxide, NiCo2O4 prepared by oxalate co-precipitation started below 400 °C as confirmed by Xray diffraction (XRD) analysis. Single phase nickel-cobalt oxide with cation ratio of 1:2 (Ni:Co) was obtained at calcination temperature of 400 °C. The spinel phase decomposed gradually until 700 °C. The calcination time for the formation of NiCo2O4 was found to be between 2 to 4 hours. The particle size of the prepared sample studied by transmission electron microscopy (TEM) showed a value of 9.5 nm. Investigation on the compositional effect of NiCo2O4 revealed that the crystallinity of the synthesized oxides improved with the increment of Ni content. The entire range of Ni:Co compositions at 400 C and 700 C were investigated with respect to the formation of phases, lattice parameter and crystallite size. Nickel-cobalt oxide series was prepared through solid-state route as well. However, NiCo2O4 co-existed with NiO in this method preparation. Moreover, solid-state route produced metal oxides with larger crystallite size than co-precipitation method. Therefore, co-precipitation served as a better method in synthesizing pure phase nanostructured NiCo2O4 compared to solid-state technique. The electrochemical properties of NiCo2O4 were measured in various acidic, neutral and alkaline electrolyte systems (1.0 M HCl, 1.0 M KCl and 1.0 M KOH) by employment of cyclic voltammetry (CV), galvanostatic charge-discharge test and electrochemical impedance spectroscopy (EIS). Ideal capacitor behaviour with the largest operating voltage of 1.0 V and good electrochemical stability were observed in NiCo2O4 using neutral KCl aqueous electrolyte. Meanwhile, the prepared sample displayed the highest surface redox activity in 1.0 M KOH alkaline electrolyte but showed the lowest electrochemical performance in acidic electrolyte. Single phase NiCo2O4 and NiMn0.5Co1.5O4 spinel powders have been synthesized by hydroxide co-precipitation method, and the effects of Mn substitution for Co have been studied. Electrodes of both materials exhibit nearly ideal electrochemical capacitor behaviour in neutral electrolyte solution (1.0 M KCl). Mn substitution greatly enhanced the specific capacitance of the spinel, giving a value of approximate 110 F g-1 due to the facile charge-transfer characteristic of the Mn ions, as revealed by in-situ X-ray absorption near-edge structure analysis. Nickel-cobalt oxide/activated carbon composite was synthesised by adapting oxalate co-precipitation synthesis protocol followed by heat treatment under an open air atmosphere. X-ray diffraction analysis confirmed that nickel-cobalt oxide spinel phase was maintained in the pure and composite phases while transmission electron microscopy revealed the nanostructured synthesis of nickel-cobalt oxide/activated carbon composite. The specific capacitance which was the sum of double-layer capacitance of the activated carbon and pseudocapacitance of the metal oxide increased with the composition of nickel-cobalt oxide before showing a decrement for heavily loaded electrodes. Utilisation of nickel-cobalt oxide component in the composite with 50 wt. % loading displayed a capacitance value of ~59 F g-1 in 1.0 M KCl. The prepared composite electrodes had good electrochemical stability upon cycling with tolerable variation in specific capacitance with increasing charge-discharge cycles.